Identifikasi Sebaran Karakteristik Kriminal di Indonesia Tahun 2021 Menggunakan Model-Based Clustering - Chrisinta, Debora; Gelu, Leonard Peter; Baso, Budiman (Journal of Mathematics, Computations and Statistics, 2022)
Crime is an aspect that affects the smooth running of the economy in society. The importance of the government's role in minimizing the occurrence of crime can be done by knowing the distribution of criminal characteristics in each province. The Model-Based Clustering method can help identify these characteristics. The Clustering process is carried out by ensuring that the distribution of variables is close to the normal distribution as seen from the QQplot and the independence of variable. The results of the Clustering show that there are two characteristics of criminality that are spread across the province of Indonesia. Identify the characteristics of the distribution of crime using the average value in each of the optimal clusters that have been obtained. The first cluster shows the distribution of 16 provinces with lower crime categories, while the second cluster shows the distribution of 18 provinces with high crime categories.